Bad Healthy State Compress Temporal Extension Both in Past and Future Orientations - Zhou, Jia; Han, Xingping; Fan, Juan; Feng, Pan; Song, Jingjing; Jiang, Guangyu; Zheng, Yong (Frontiers in Psychology, 2018)
We examined how different health states and cancer-related depression influence time perception in temporal extension regarding the past and the future over individuals’ entire lives. We used the magnitude estimation method to investigate temporal extension (past and future) and long duration (20 years), and directly measured patients with cancer and their subjective feelings about their lives. In Experiment 1, we investigated whether there were differences in perceptions of temporal extension between patients with cancer (n = 144) compared to a healthy control group (n = 208). Results indicated that the patients with cancer group evaluated longer temporal extension in healthy states (imagination condition) than in unhealthy states (objectivity condition), and the healthy control group evaluated longer temporal extension in healthy states (objectivity condition) than in unhealthy states (imagination condition). Moreover, the patients with cancer group evaluated longer past-oriented temporal extension than future-oriented temporal extension, whereas the healthy control group evaluated longer future-oriented temporal extension than past-oriented temporal extension. Experiment 2 was conducted to further examine the unexplained findings of Experiment 1. Results indicated that because of the impact of depression on the cancer group, their embodied time system slowed down, and explicit behavior indicated an over-evaluation of time, resulting in group differences. In conclusion, temporal extension could be affected by different health states. Moreover, healthy and unhealthy states may be more associated with future and past orientation, respectively. Lastly, individuals’ time perception can be influenced by depression.